2016
DOI: 10.1681/asn.2015080909
|View full text |Cite
|
Sign up to set email alerts
|

Immune-Regulatory Molecule CD69 Controls Peritoneal Fibrosis

Abstract: Patients with ESRD undergoing peritoneal dialysis develop progressive peritoneal fibrosis, which may lead to technique failure. Recent data point to Th17-mediated inflammation as a key contributor in peritoneal damage. The leukocyte antigen CD69 modulates the setting and progression of autoimmune and inflammatory diseases by controlling the balance between Th17 and regulatory T cells (Tregs). However, the relevance of CD69 in tissue fibrosis remains largely unknown. Thus, we explored the role of CD69 in fibrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 55 publications
(61 reference statements)
0
35
0
Order By: Relevance
“…Fibrosis development was also accompanied by a slight reduction in regulatory T cells (Treg). This anti-inflammatory T cell subset controls T cell expansion, including of inflammatory Th17 cells, which are known to be involved in peritoneal damage and fibrosis development 22 . The percentage of Th17 cells, however, was not affected (Figure 8c).…”
Section: Prevention Of Pds-induced Peritoneal Fibrosis Development Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Fibrosis development was also accompanied by a slight reduction in regulatory T cells (Treg). This anti-inflammatory T cell subset controls T cell expansion, including of inflammatory Th17 cells, which are known to be involved in peritoneal damage and fibrosis development 22 . The percentage of Th17 cells, however, was not affected (Figure 8c).…”
Section: Prevention Of Pds-induced Peritoneal Fibrosis Development Inmentioning
confidence: 99%
“…Parietal peritoneal membrane biopsies obtained from the opposite side of the catheter were processed as previously described 22 . Briefly, membranes were fixed (Bouin solution), embedded in paraffin, cut into 5-µm sections, and stained (Masson's Trichrome stain).…”
Section: Peritoneal Membrane Histologymentioning
confidence: 99%
“…13,14 Experimental modulation of the Th17 response and/or enhancing the regulatory T cell (Treg) response may preserve membrane function. [15][16][17] Thus, chronic inflammatory damage of the peritoneal membrane can be modulated, at least in part, through regulation of the Th17/Treg balance. 18 Other cytokines are linked to specific PD-associated patient subgroups and characteristics.…”
Section: Biomarker Research In the Context Of Chronic Peritoneal Inflmentioning
confidence: 99%
“…It has been recently demonstrated that the leukocyte antigen CD69 controls fibrosis by regulating Th17 response, so it represents a new, yet unexplored, therapeutic target [84].…”
Section: Modulating Specifically Th17/t Regulatory Responsesmentioning
confidence: 99%